Comparative study of hsC-reactive protein nd lipid profiles of members of four Filipino families suspected with familial hypercholesterolemia - Paladar, Elde Mel B.
C-reactive protein and LDL-cholesterol have a strong linear relation with the incidence of cardiovascular disease (Ridker, 2002). However, Familial Hypercholesterolimia (FH) patient-based data directly comparing these two biologic markers are not available.In this study total cholesterol, HDL cholesterol (HDLc), LDL cholesterol (LDLc) and high sensitive C-reactive protein (hsCRP) profiles of members of four Filipino families suspected with FH and age-and gender-matched normal healthy individuals were measured and compared, in order to determine if lipid profile is directly related with hsCRP level in FH patients.The study initially surveyed some 32,800 patients from the blood chemistry records of the five cooperating hospitals. From these, 352 were found hypercholesterolimic based on their total cholesterol. From the 352, 60 individuals were suspected with FH based on high total cholesterol and LDL cholesterol, history of cardiovascular disease in the family, and normal blood sugar and creatinine. From the 60, 17 subjects belong to four (4) Filipino families. These 17 individuals composed the final population of this study. Seventeen normal, healthy Filipinos, age-and gender-matched of the 17 subjects suspected with FH were recruited to be normal control in the study.
In this study, it was found that among the 17 subjects suspected with FH, the incidence of FH was higher in males than in females. All 17 subjects suspected with FH exhibit cholesterol values consistent with patients diagnosed with FH. The rise of serum total cholesterol and LDLc levels appeared to generally increase with age as observed among ages 50-60 where mean cholesterol levels were highest.The mean total cholesterol:HDL cholesterol (TC:HDLc) ratio among the FH subjects in this study was 12:1 while among normal healthy subjects it was 4:5:1. Using the Quintile of cardiovascular diseases (CVD) risk to evaluate TC:HDLc ratio, 16 of the 17 subjects suspected with FH have TC:HDLc ratio falling on quintile 5, being the highest risk for CVD relative risk category, while among normal healthy subjects only one was on quintile 5, while five, four and six subjects fell on quintiles 4, 3 and 2 respectively. This data may suggest that the suspected FH subjects are at greater odds developing CHD.High sensitivity CRP is an inflammatory marker believed to be of value in the prediction of coronary events. The mean hsCRP (3.92 mg/L) among the subjects suspected with FH was not statistically different from the mean (3.00mg/L) of normal healthy subjects. High sensitive-CRP data were interpreted based on "quintiles of CVD risk," a series of five clinical cutpoints wherein the relative risks of sustaining CVD increases in a stepwise fashion with quintile 1 (0.1-0.7 mg/L) and quintile 5 (3.9-15 mg/L) being the lowest risk and highest risk respectively (Ridker, 2002). Eight of the 17 subjects suspected with FH fell on quintile 5 and seven on quintile 4. This means about 76 percent of subjects suspected with FH and about 70 percent of the normal healthy individuals are at high risk for future cardiovascular events. Age and gender showed no significant relationship with hsCRP levels.
In this study eight of the 17 subjects suspected with FH have 8.7 fold, and six subjects have 7.2 fold higher relative risk (RR) of CVD than those in the lowest quintile when hsCRP and TC:HDLc ratio were combined. This observation may suggest that the FH subjects in this study are at greater risk of cardiovascular event. The result also shows dramatic increase in RR of CVD when hsCRP RR is combined with TC:HDLc RR; wherein mean RR of CVD based on TC:HDLc ratio alone was 4, while it dramatically increases to 7.4 when combined. This observation may suggest that when hsCRP value is utilized with lipid values, the CVD risk prediction is better.The FH subjects' total cholesterol and LDLc levels were weakly correlated with hsCRP levels, which may thus suggest each of these parameters may identify different high-risk groups for cardiovascular disease.
Thesis (MS Biochemistry)--University of the Philippines Manila
Keywords: C-reactive protein; Lipids; Hypercholesterolemia; Hypercholesteremia